Accelerating Taylor bubbles within circular capillary channels: Break-up mechanisms and regimes. (January 2021) - Andredaki, Manolia; Georgoulas, Anastasios; Miché, Nicolas; Marengo, Marco
Highlights: Enhanced VOF modelling for accelerating Taylor Bubbles within capillaries. Prevailing Taylor Bubble break-up regimes are identified and quantified for the first time. Interfacial phenomena that are difficult to be observed in experiments are revealed. Novel mapping of break-up regimes according to global dimensionless flow parameters. Abstract: In the present paper, an enhanced Volume of Fluid model is applied for the conduction of parametric numerical simulations, to investigate break-up phenomena of accelerating, elongated, vapour bubbles, within circular mini-channels. The effect of fundamental controlling parameters in the resulting break-up characteristics is investigated. Four different series of parametric numerical simulations of isolated vapour bubbles within mini-channels are performed, examining the effects of the imposed pressure difference between the inlet and the outlet of the channel, the surface tension, the effect of the applied heat flux as well as the initial liquid film thickness between the bubbles and the channel, on the developed vapour/liquid interface dynamics. The overall dimensionless number ranges examined are 6.76 < We < 1474.7, 0.007 < Ca < 0.14, 694 < Re < 12541 and by introducing a modified Froude number in order to account for the flow acceleration, 1 < Fr* < 21.86. These dimensionless number ranges are selected in order to overlap with experimental observations in zero-gravity Pulsating Heat Pipe experiments that constitute the motivation for the present numerical investigation. The proposed simulation results identify three prevailing regimes. A "full break-up" regime, a "partial break-up" regime and a "no break-up" regime. The entrainment of liquid droplets at the trailing edge of the vapour slugs is in most cases responsible for their subsequent "full break-up", into a leading and a trailing bubble, as it is identified from the numerical simulations. Moreover, the applied heat flux does not influence the resulting break-up regimes. Finally, these identified break-up regimes, are grouped together into a well-defined flow map with respect to the We and Fr* numbers.